2019
DOI: 10.1021/acs.iecr.9b00465
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Micromixing of Non-Newtonian Fluids by a Novel Zigzag Punched Impeller

Abstract: In this work, a novel impeller with zigzag punched blades is developed to produce impinging jet streams from face-to-face holes to enhance mixing in a 0.282 m diameter baffled stirred tank. The micromixing experiments on non-Newtonian fluids are conducted to compare among standard six straight blade turbine (DT), down-pumping pitched blade turbine (PBTD-45°) and our novel zigzag punched impeller (ZPI). Results show that at low Reynolds numbers (700 < Re < 3000), the segregation index of ZPI is the lowest. It s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Many authors have investigated the kinetic models of these reactions. In the past 3 years, the kinetic models developed by Guichardon and Falk are still the most widely used models in various mixing devices, including the stirred tank, microchannel reactor, high-speed disperser, rotating packed bed, spinning disc reactor, high-shear mixer, and so on. To compare conveniently with other mixing devices, we also employ these kinetic models. …”
Section: Experimental Methods and Apparatusmentioning
confidence: 99%
“…Many authors have investigated the kinetic models of these reactions. In the past 3 years, the kinetic models developed by Guichardon and Falk are still the most widely used models in various mixing devices, including the stirred tank, microchannel reactor, high-speed disperser, rotating packed bed, spinning disc reactor, high-shear mixer, and so on. To compare conveniently with other mixing devices, we also employ these kinetic models. …”
Section: Experimental Methods and Apparatusmentioning
confidence: 99%
“…The hydrodynamics of solid-liquid suspension process in the stirred tank with a dual rigid impeller, a dual rigid-flexible impeller, and a punched rigid-flexible impeller was numerically simulated by Gu et al, 9 indicating that the punched impeller can produce a series of jet flows in the rotation process, and the jet flows could form a variety of vortices to enhance the turbulence extent of the mixing system. Yang et al 10 developed a novel zigzag punched impeller (ZPI) and found through experiment that the ZPI can not only reduce power consumption but also produce efficient impinging streams to disturb regular circular motion of the fluid, and its mixing outperforms the standard six straight blade turbine and down-pumping pitched blade turbine. Through these investigations, it is found that the reasonable design of the punched impeller can improve the mixing performance of solid-liquid suspension.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al [17] investigated the effects of blade shape on trailing vortices, indicating that trailing vortices could provide a source of turbulence and have a potential benefit for mixing in a stirred tank. Yang et al [18] developed a novel zigzag punched impeller with promising outcomes. Another alternative is based on cut blade surfaces.…”
Section: Introductionmentioning
confidence: 99%